Effects of BCAA Enteral Nutrition to the Change of Nutritional Status and Hepatic Encephalopathy Parameters in Liver Cirrhosis Patient with Hepatic Encephalopathy - Achmad Fauzi; Unggul Budihusodo; Nurul Akbar; Pradana Suwondo; Suhardjono Suhardjono; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2009)
Background: This study was also conducted to determine the effects of high-branched chain amino acid (BCAA) enteral supplementation on altered nutritional status parameters (including plasma prealbumin) and hepatic encephalopathy parameters in liver cirrhosis patients with hepatic encephalopathy. Method: Our study was a randomized, single-blinded experimental study comparing between control group of liver cirrhosis patients with standard hospital liver diet (40 kcal/kgBW/day for male and 35 kcal/kgBW/day for female; protein 1.25 g/kgBW/day) and experimental group of liver cirrhosis patients with liver diet modification high in BCAA supplementation, which had similar protein and calorie calculation as the control group. Results: Subclinical hepatic encephalopathy prevalence was 32%. In the experimental group, prealbumin plasma, arm circumference, body weight and body mass index (BMI) increased; whereas in the control group, prealbumin plasma, arm circumference, body weight and BMI decreased (p 0.05). In experimental group, the ammonia level significantly decreased (p 0.01). Clinical hepatic encephalopathy, flapping tremor, the number connection test (NCT) did not show significant changes between the two groups. However, there was worsening trend in the control group. Level of albumin, bilirubin, AST, ALT did not show any significant difference between both groups. Conclusion: High-BCAA enteral supplementation which is administered to liver cirrhosis patients with hepatic encephalopathy for 14 days could improve plasma prealbumin level, arm circumference, body weight, BMI and could decrease the plasma ammonia level. However, it does not improve Fischer ratio, psychometric test and electroencephalography Keywords: malnutrition, liver cirrhosis, BCAA, Fisher ratio